2013
DOI: 10.1177/1420326x13500294
|View full text |Cite
|
Sign up to set email alerts
|

A review of membrane-based air dehumidification

Abstract: Air dehumidification plays an important role in improving air quality and maintaining thermal comfort. Increasing attention is paid to the membrane-based technology, which is based on water vapour transmembrane transport driven by mass transfer potential, together with sensible heat transfer under temperature difference. Membrane-based air dehumidification has been applied in heating, ventilation and air conditioning, compressed air dehumidification and environmental control in space vehicle, and some other en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(32 citation statements)
references
References 93 publications
(171 reference statements)
0
32
0
Order By: Relevance
“…Transfer parameters such as permeance and selectivity are dictated by the membrane solubility and diffusivity properties. PVA polymer has been one of the popular choices of material for these membranes due to its hydrophilic properties, stability and ease of film formation [2,8,12,19,23,24,28]. The modification of PVA using lithium chloride to enhance water permeability has been reported [12,19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Transfer parameters such as permeance and selectivity are dictated by the membrane solubility and diffusivity properties. PVA polymer has been one of the popular choices of material for these membranes due to its hydrophilic properties, stability and ease of film formation [2,8,12,19,23,24,28]. The modification of PVA using lithium chloride to enhance water permeability has been reported [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, hydrophilic polymer has attracted much attention due to its high water permeability and selectivity [2,4,[6][7][8]12,[17][18][19][23][24][25][26]. These are usually dense membranes for which water vapor transfer is based on solution-diffusion mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent reviews, Woods 15 and Zhang 16 provided overviews of the latest membrane developments in HVAC and a summary of potential avenues for future research, while another review by Yang et al 17 highlighted the major advances membrane technology has made in air dehumidification. In search of membranes with the greater selectivity necessary to make this process viable, Zhang et al 18 developed a novel membrane using a polyethersulfone (PES) support layer coupled with a polyvinylalcohol (PVA) active layer, while Bui et al 19,20 later reported the fabrication of a robust hydrophilic PVA/LiCl composite membrane.…”
Section: Introductionmentioning
confidence: 99%